Who Should Have Children? (Us?) When Should We Have Children? (Now?) - Beran, Ondřej (My University, 2022)
This paper has two main parts. First, it overviews the topic of environmental grief and related emotions. Specifically, it stresses the need to think of emotions in at least partly cognitive terms (as forms of understanding) and to consider an existential rather than medical account of environmental emotions (despite using terms such as anxiety). The second part is a reflection on the currently endemic worries about having children. I will argue that it is misplaced to analyse this attitude universally as an argument-based decision. Rather, if it relates to environment grief, the emotion may be providing a reason for this attitude, or be expressed as the attitude. The misleading ‘argument’ framing and the near-condescending responses to it may be related to a specifically generational failure of understanding.
Kdo má mít děti? (My?) Kdy máme mít děti? (Teď?)
Keywords: environmental grief; parenthood; perception; condescension